Phytoplankton Composition and Productivity of a Shallow Tropical Lake - Md Yusoff, Fatimah; Mohammad Mohsin, Abu Khair; Abdul Satar, Mustafa Kamal (1984)
Phy toplankton composition and production in Paya Bungor, Pahang, were studied from October 1981 to Septemoer 1982 and from January to December 1982 respectively. Phytoplankton diversity is in the order of Chlorophyta> Bacillariophyceae > Cyanophyta> Chrysophyceae > Euglenophyta > Phyrrhophyta; but the order in terms or ab~ndance is Cyanophyta> Chrysophyceae > Chlorophyceae> Bacillariophyceae. The brown water system of Paya Bungor seems to contain a higher phytoplankton production than the white water system. Maximum production generally occurs at the top layer of the water, but shifts to the subsurface layers on hot days due to photo-inhibition at the surface. Generally, nutrient and light energy are the two most important factors controlling phytoplankton production in Paya Bungor.